Characteristics Companies Against Tax Avoidance - Siswadi Sululing; Nurcahya Hartaty Posumah (Proceeding of The International Conference on Business and Economics, 2023)
Numerous businesses are capable of implementing a wide range of tax planning techniques. Tax avoidance, or legally lowering taxes, is one tax planning tactic. Tax avoidance strategies typically use loopholes in the tax code without breaking any of them. In addition, they use tax law gaps to perpetrate tax evasion. While this tax evasion tactic is legal, the corporation using it is still receiving funding from the state. In 2013, 832 foreign investment companies were suspected of engaging in tax fraud in Indonesia due to their five consecutive years of loss reporting and nonpayment of taxes. This study aims to investigate and evaluate the effects of capital intensity, profitability, leverage, and majority share ownership on tax evasion. The Current Effective Tax Ratio is used in this study to generate tax avoidance. Mining businesses that are listed on the Indonesia Stock Exchange for the period of 2017–2021 make up the population and sample for this study. With 37 observational data points, 7 mining companies make up the research sample. A multiple linear regression model is the research methodology employed in this study. Version 22 of the IBM Statistical Package for Social Science was used to process the data for this study. The study's findings demonstrate that tax evasion is not much impacted by profitability or leverage. Conversely, capital intensity and majority share ownership have a detrimental impact on tax evasion.